Impaired mobility, depressed mood, cognitive impairment and polypharmacy are independently associated with disability in older cancer outpatients: The prospective Physical Frailty in Elderly Cancer patients (PF-EC) cohort study. Issue 3 (May 2017) - Pamoukdjian, Frederic; Aparicio, Thomas; Zelek, Laurent; Boubaya, Marouane; Caillet, Philippe; François, Veronique; de Decker, Laure; Lévy, Vincent; Sebbane, Georges; Paillaud, Elena
Abstract: Objective: To assess the prevalence of disability and the oncologic factors associated with disability in older outpatients with cancer. Materials and Methods: The Physical Frailty in Elderly Cancer patients (PF-EC) study (France) is a prospective bicentric observational cohort study. Two hundred and ninety outpatients with cancer were included. A cross-sectional analysis of oncologic factors and geriatric variables associated with disability that were collected using a comprehensive geriatric assessment (CGA) was conducted. Disability was defined as impairment in activities of daily living (ADL) and/or instrumental activities of daily living (IADL), simplified to four items. Univariate and multivariate logistic models of disabled patients were performed. The three final multivariate models were compared using the area under the receiver operating characteristic curve (AUC/ROC) of the logistic model. Results: The mean age was 80.6 years, and 51% of the patients were women with various types of cancer. The prevalence of disability was 67.6%. No oncologic factors (cancer site, cancer extension) were associated with disability. Impaired mobility, poor functional status, depressive mood, cognitive impairment and polypharmacy were independently associated with disability ( P < 0.05). The AUC/ROC of the final models was similar. Conclusion: Disability was highly prevalent in older cancer outpatients before cancer treatment but was not associated with oncologic factors. Impaired mobility, depressed mood, cognitive impairment and polypharmacy were the geriatric variables significantly and independently associated with disability. Identifying these factors prior to cancer treatment could enable the implementation of corrective actions to improve patient autonomy before treatment and during follow-up.